2019
DOI: 10.1111/dth.12909
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe psoriasis with ixekizumab in a liver transplant recipient with concomitant hepatitis B virus infection

Abstract: Treatment of severe psoriasis (PsO) in organ transplant (OT) patients is difficult. In fact, systemic drugs used for PsO therapy can be detrimental to transplanted organs and/or can increase the risk of serious infections in subjects already taking antireject medicines. Current guidelines fail to give indications on how to manage PsO OT subjects. Moreover, only a few cases of patients with the above‐cited characteristics treated with systemic therapies have been published so far. Here, we report our experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
0
14
0
4
Order By: Relevance
“…A case report on a patient with CHB treated with ixekizumab and entecavir simultaneously did not develop HBVr after 18 mo of treatment[ 53 ]. Another report showed that a patient with resolved HBV did not experience HBVr during follow-up (Table 2 )[ 54 ]. Given that data regarding the risk of HBVr in patients treated with ixekizumab or brodalumab are still limited, further studies with larger sample sizes are warranted.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…A case report on a patient with CHB treated with ixekizumab and entecavir simultaneously did not develop HBVr after 18 mo of treatment[ 53 ]. Another report showed that a patient with resolved HBV did not experience HBVr during follow-up (Table 2 )[ 54 ]. Given that data regarding the risk of HBVr in patients treated with ixekizumab or brodalumab are still limited, further studies with larger sample sizes are warranted.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…Cases of chronic or resolved HBV infection in patients undergoing secukinumab therapy have been reported [ 86 , 87 ], but none were found to have hepatitis or virus reactivation. A good safety profile was shown also for ixekizumab: 2 reports in the literature (one with active HBV infection and concurrently treated with entecavir and one with both markers of past HBV infection and anti-HCV positivity and no signs of reactivation) suggest the drug as safe in this setting [ 88 , 89 ]. No cases of reactivation of HBV have been reported in randomized controlled trials of brodalumab and its safety has not been yet established in HBV or HCV patients by real-world data [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no guidelines for treatment of moderate‐to‐severe psoriasis in OTRs and only scattered information on the use of biologics in conjunction with immunosuppressive regimen have been reported in the literature. An improvement of the disease, with no side effects, has been reported in five OTRs affected by psoriasis treated with etanercept (anti‐TNFα drug) 2‐4 and in one patient treated with ixekizumab (anti IL‐17 drug) 5 . To the best of our knowledge, this is the first case of psoriasis in OTRs treated with ustekinumab (anti IL‐12/‐23 drug) with a rapid and complete resolution of the disease without any side effects at 6‐months follow‐up.…”
Section: Figurementioning
confidence: 94%
“…An improvement of the disease, with no side effects, has been reported in five OTRs affected by psoriasis treated with etanercept (anti-TNFa drug) [2][3][4] and in one patient treated with ixekizumab (anti IL-17 drug). 5 To the best of our knowledge, this is the first case of psoriasis in OTRs treated with ustekinumab (anti IL-12/-23 drug) with a rapid and complete resolution of the disease without any side effects at 6-months follow-up.…”
mentioning
confidence: 85%